(untitled) (Bangladesh Journal of Urology, 2023)
Objective: Percutaneous nephrolithotomy (PCNL) is a safe and effective treatment modality for patients with renal stones, regardless of the history of previous surgery. For patients who have been previously treated for renal stones, half of them will face stone recurrence within 5-7 years. The objective is to evaluate the renal functional status following percutaneous nephrolithotomy in patients with previously operated renal calculi. Materials and Methods: From July 2018 to June 2020, previously operated total 44 selected recurrent renal calculi patients underwent standard PCNL. Serum creatinine and renal 99mTc-DTPA scan were done pre-surgery and at post-operative 3 month and year 01, respectively. An assessment was done on renal function, comparing pre and post-operative values. Institutional ethical committee clearance was taken before the commencement of the study. Results: Among 44 patients, 29 patients (65.9%) had a previous history of open stone surgery, and 15 patients (34.09%) underwent PCNL previously. Mean pre and postoperative serum creatinine were not significant between the cohorts (p=0.28). Mean pre-operative split renal functions (in 99mTc-DTPA) of patients (45.13±14.14%) were found almost stable in comparison to mean post-operative value (44.38±10.96%) and (46.99±9.66%) in 03 and 12-month follow-up respectively. Mean GFR for pre-operative and post-operative values were 42.23±6.03 mL/min, 45.93±5.47 mL/min, and 48.99±5.87 mL/min, respectively, which were not statistically significant. Based on serum creatinine and DTPA nuclear renogram, patients showed stability or improvement in renal function at post-operative follow-up. Summarily, a normal pre-operative serum creatinine, regardless of history of previous surgery, maintained stability rather than deterioration in renal function. Conclusions: PCNL is an effective treatment modality in patients with previously operated renal calculi as parameters of renal function had remained stable or slightly improved in the majority of patients on post-operative follow-up. Bangladesh J. Urol. 2022; 25(1): 28-32